Comparison of Biochemical, Hematological Parameters and Pesticide Expose-related Symptoms among Organic and Non-organic Farmers, Singburi, Thailand - Sudjaroen, Yuttana (Asian Journal of Pharmaceutics (AJP), 2017)
Background: Main of agriculturists in Singburi was cultivated rice and major pesticidesâ€™ use is chlorpyrifos; however, farmers are applied bio-extracts to eliminate pest and trend to be organic farming. Hence, organic farmers may become lower risks from pesticides rather than non-organic farmers. Aim: To determine biochemical and hematological status between organic and non-organic farmers, Bang Rachan district, Singburi, Thailand. Materials and Methods: Farmers were separated into organic farmer group (N = 35) and non-organic farmer group (N = 45). Individual data for pesticide exposure were included, and pesticide-exposed relating symptoms were recorded. All demographic data of participants were documented before blood collection. Serum samples were analyzed for butyrylcholinesterase (BuChE) activity, liver function test, kidney function test, and lipid profiles. Each ethylenediaminetetraacetic acid-whole blood was determined for complete blood count (CBC). NaF plasma was analyzed for determine fasting blood glucose. All biochemical parameters were principled according to enzymatic assays and CBC was automatic analyzers. The data were represented in average Â± standard deviation, and difference of biochemical and hematological status of two groups was statistically tested by unpaired t-test (P < 0.05). Results and Discussion: Blood glucose and lipid profiles of non-organic farmers were higher than reference ranges and significantly difference with other groups. Mean corpuscular hemoglobin (MCH) and MCH concentration values of non-organic farmers were lower than reference range and interpreted as anemia. Conclusions: Non-organic farmers were suchronic pesticide exposure with normal BuChE values and no related symptom; therefore, subclinical symptoms were disturbed biochemical and hematological status; and prediabetes, dyslipidemia, and anemia appeared.